Formative experiences and psychological distance in the lives of contemporary environmentalists - Raja, Urooj S.; Carrico, Amanda R. (Frontiers in Psychology, 2023)
Introduction We use the term “environmentalists” to describe the people who are highly and actively engaged and involved in environmental issues like climate change. Environmentalists consistently advocate, research, or volunteer to do the work needed to address environmental challenges. Factors that drive contemporary environmentalists remain understudied. Methods We, therefore, ask: what formative experiences drive environmentalists on climate change and other environmental problems at present? We frame this exploration through the significant life experiences (SLE) literature, which examines people and environmental pathways. We also ask: how do feelings of perceptual/actual distance or closeness to environmental threats and climate change shape a person’s decision to become an environmentalist? We anchor this query to the psychological distance (PD) literature that explores how people perceive external phenomena and the role distance plays in their conception. To answer both questions, we use qualitative methods and draw on 33 interviews with environmentalists involved in environmental protection work for an average of 91 h in the past 4 weeks. Results We find that environmentalists spoke about several formative experiences broadly consistent with what has been documented in the SLE literature. Traumatic experiences were especially influential for our sample of environmentalists. Our findings also reveal that PD, especially social, plays a role in the lives of environmentalists. Discussion Study findings could help scholars and practitioners deepen their understanding of contemporary environmentalists. Practitioners, in particular, could use this knowledge to help environmentalists by providing them with tailored resources and support.